1993
DOI: 10.1016/0190-9622(93)70206-9
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis in Australian twins

Abstract: PURPOSE:Appendicitis is an inflammation of the appendix, the etiology of which is still poorly understood. Previous studies have shown an increased risk for cigarette smokers but no accounts for the timing of exposure to smoking relative to appendectomy were made. METHODS: Based on questionnaire data, both cohort and co-twin case-control analyses were conducted to assess the effect of active cigarette smoking on appendectomy in 3808 Australian twin pairs. Smoking status was defined as a time-dependent covariat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
105
3
6

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(119 citation statements)
references
References 23 publications
4
105
3
6
Order By: Relevance
“…In this way IFN-g may play a major role in enhancing the IL-17 response (4). Psoriasis has a strong genetic component, with a 40-70% concordance in identical twins (7,8). Several susceptibility alleles have now been identified and confirmed (9), and HLA-Cw*0602 has recently been implicated as the strongest susceptibility allele in psoriasis (10).…”
mentioning
confidence: 99%
“…In this way IFN-g may play a major role in enhancing the IL-17 response (4). Psoriasis has a strong genetic component, with a 40-70% concordance in identical twins (7,8). Several susceptibility alleles have now been identified and confirmed (9), and HLA-Cw*0602 has recently been implicated as the strongest susceptibility allele in psoriasis (10).…”
mentioning
confidence: 99%
“…Its prevalence in Western populations is estimated to be around 2 -3% (Gudjonsson and Elder, 2007). The cause of psoriasis is poorly understood, but is believed to include a genetic component (Brandrup et al, 1982;Duffy et al, 1993;Krueger and Ellis, 2005); concordance in monozygotic twins is about 70%, whereas in dizygotic twins this is only 20% (Krueger and Ellis, 2005). Psoriasis is an immune-mediated disorder, for which T cells are abnormally activated to release cytokines, which cause inflammation and rapid production of skin cells (Griffiths and Voorhees, 1996).…”
mentioning
confidence: 99%
“…19 Yet other studies found leveling off or even drastically declining rates of psoriasis prevalence for individuals beyond the age of 70 years compared to younger age classes. 17,[21][22][23][24][25] Thus, in contrast to the relatively high prevalence measured herein, a nation-wide telephone survey in Spain applying essentially the same structured questionnaire recorded only 0.33% age-specific prevalence in persons >70 years old. This was only a quarter of the average psoriasis prevalence measured in the whole target population of this latter study or just one seventh of the highest prevalence rate that was found for age 17 Telephone surveys answered by proxies is a reliable and generally valuable source of information about health conditions of older probands.…”
Section: Discussionmentioning
confidence: 99%